2017
DOI: 10.1289/ehp142
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Prenatal Exposure to Perfluorinated Chemicals with Glucocorticoid and Androgenic Hormones in Cord Blood Samples: The Hokkaido Study

Abstract: Background:Perfluorinated chemicals (PFCs) disrupt cholesterol homeostasis. All steroid hormones are derived from cholesterol, and steroid hormones such as glucocorticoids and androgenic hormones mediate several vital physiologic functions. However, the in utero effects of PFCs exposure on the homeostasis of these steroid hormones are not well understood in humans.Objectives:We examined the relationship between prenatal exposure to perfluorooctane sulfonate (PFOS)/perfluorooctanoate (PFOA) and cord blood level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 58 publications
0
40
1
Order By: Relevance
“…PFOS, but not PFOA were inversely correlated with maternal TSH and positively associated with infant serum TSH (Kato et al 2016). Similarly, PFOS, but not PFOA was negatively associated with glucocorticoids in cord blood (Goudarzi et al 2017).…”
Section: Minatoyamentioning
confidence: 78%
See 1 more Smart Citation
“…PFOS, but not PFOA were inversely correlated with maternal TSH and positively associated with infant serum TSH (Kato et al 2016). Similarly, PFOS, but not PFOA was negatively associated with glucocorticoids in cord blood (Goudarzi et al 2017).…”
Section: Minatoyamentioning
confidence: 78%
“…Potential confounding variables were considered based on the previous literatures (Itoh et al 2016;Kato et al 2016;Goudarzi et al 2017). Medical record and questionnaires were used for obtaining data.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…DHEA decreased (Q4 vs. Q1: β = − 1.23 ng/mL, 95% CI − 1.72 to − 0.25) in association with PFOA. [ 44 ] DEHP Cord reproductive hormones 202 MEHP was associated with reduced levels of T/E2, P4, and inhibin B. Inverse associations between maternal MEHP levels T/E2, P4, inhibin B, and INSL3 for males. [ 42 ] Cord steroid hormones 202 MEHP was associated with reduced cortisol and cortisone levels and glucocorticoid/adrenal androgen ratio whereas increased DHEA levels and DHEA/androstenedione ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our findings, Apelberg et al (2007) reported that the multiparous births group has lower PFOA concentrations than primiparous births (p = 0.02) in 299 cord blood samples from the Baltimore THREE Study in -2005 also indicated a correlation between parity and cord PFOA levels among 70 South Koreans (OR = 0.32, 95% CI 0.1, 1.05). Many studies demonstrated a negative correlation between PFOA in maternal and parity (Goudarzi et al 2016;Kato et al 2014;Kishi et al 2015;Lee et al 2016), and concentrations of PFOA in cord serum were highly correlated with those in maternal serum Needham et al 2011). Perhaps these findings partly explain the difference of cord PFOA concentration due to parity.…”
Section: Isomeric Profile Of Pfoa In Cord Serummentioning
confidence: 97%